2009
DOI: 10.1177/003804070908200404
|View full text |Cite
|
Sign up to set email alerts
|

Another Way Out: The Impact of Juvenile Arrests on High School Dropout

Abstract: This article suggests that contact with the legal system increased school dropout in a Chicago sample of 4,844 inner-city students. According to multilevel multivariate logistic models, students who were first arrested during the 9th or 10th grade were six to eight times more likely than were nonarrested students ever to dropout of high school and are about 3.5 times more likely to drop out in Grades 9 and 10. However, selection bias is a real concern. To improve causal inference, students who were first arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 56 publications
(93 reference statements)
4
78
0
9
Order By: Relevance
“…For instance, Kirk and Sampson (2013) appended data on arrests from police records to longitudinal survey data from the Project on Human Development in Chicago Neighborhoods. Their results showed that an arrest during the high school years heightened the probability of dropping out, controlling for other factors (see also Hirschfield, 2009). Administrative data also were used to demonstrate an association between dropping out and hospitalization (van Heesch, Bosma, Traag, & Otten, 2012), foster care placement (Vinnerljung, Öman, & Gunnarson, 2005), parental imprisonment (Cho, 2011), as well as changes in family income and maternal employment (Randolph et al, 2006).…”
Section: Prospective Longitudinal Studies Of General Adolescent Develmentioning
confidence: 99%
“…For instance, Kirk and Sampson (2013) appended data on arrests from police records to longitudinal survey data from the Project on Human Development in Chicago Neighborhoods. Their results showed that an arrest during the high school years heightened the probability of dropping out, controlling for other factors (see also Hirschfield, 2009). Administrative data also were used to demonstrate an association between dropping out and hospitalization (van Heesch, Bosma, Traag, & Otten, 2012), foster care placement (Vinnerljung, Öman, & Gunnarson, 2005), parental imprisonment (Cho, 2011), as well as changes in family income and maternal employment (Randolph et al, 2006).…”
Section: Prospective Longitudinal Studies Of General Adolescent Develmentioning
confidence: 99%
“…As aquisições escolares durante o período de internação também se mostraram associadas a menores taxas de evasão escolar posterior e as de reincidência na prática de delitos, conforme estudo de Blomberg, Bales e Piquero (2012). Hirschfield (2009), ao pesquisar os possíveis efeitos da passagem pelo Sistema de Justiça na experiência escolar de adolescentes, averiguou o incremento da evasão escolar, provavelmente devido à rotulação e à exclusão dos adolescentes no ambiente escolar, por conta do estigma gerado pelo rótulo de infrator. Os resultados também indicaram a aplicação de punições mais severas a esses alunos.…”
Section: ) a Evasão Escolar E A Conduta Infracionalunclassified
“…Além de gerar gastos públicos com o Sistema de Segurança e de Justiça Juvenil, bem como prejuízos econômicos e psicossociais às vítimas e à sociedade em geral (LeBlanc, 2003;Maschia, Hatcher, Schwalbe & Rosato, 2008;Ward et al, 2010), a atividade infracional na adolescência implica, muitas vezes, em experiências negativas e na exposição dos jovens infratores a situações de risco, que podem impactar e comprometer seu desenvolvimento psicossocial (Hirschfield, 2009). …”
Section: Introductionunclassified
“…Tomando por base estas considerações, diversos trabalhos se propuseram a investigar as conexões existentes entre a evasão escolar e o envolvimento com a prática de atos infracionais (Blomberg et al, 2011;Chui & Chan, 2012;Cruise, Evans, & Pickens, 2011;Dembo et al, 2012;Estevam et al, 2009;Ford & Schroeder, 2011;Gagnon, Barber, Van Loan, & Leone, 2009;Geib et al, 2011;Hirschfield, 2009;Hjalmarsson, 2008;Li & Lerner, 2011;Liljeberg et al, 2011;Mallett, 2010;Mottus, Guljajev, Allik, Laidra, & Pullmann, 2012;Natsuaki et al, 2008;Rocque & Paternoster, 2011;Sabates, 2008;Shandra & Hogan, 2012;Suh et al, 2007;Toldson et al, 2010;Zhang et al, 2010;Zhang, Katsiyannis, Barrett, & Willson, 2007).…”
Section: A Importância Da Variável "Fraca Vinculação Escolar" Para a unclassified
“…O afastamento da escola configura-se em um marco importante para a entrada ou para o agravamento da conduta delituosa, porque parece tornar os adolescentes mais vulneráveis, pelo tempo ocioso, sem supervisão, e pela possibilidade aumentada de ligação a pares divergentes, no período sem atividades (Ford & Schroeder, 2011;Hirschfield, 2009;Janosz & LeBlanc, 1999;LeBlanc, 1996;Liljeberg et al 2011;Patterson et al, 1992;Weerman, 2010;Zhang et al, 2010). Ademais, estar fora da escola parece aumentar a vigilância das agências oficiais de controle (polícia) sobre tais adolescentes, o que incrementa as chances deles serem pegos e apreendidos, gerando um ciclo de consequências negativas, que pode piorar a situação educacional dos mesmos (Bazon, Komatsu, Panosso, & Estevão, 2011).…”
Section: Tabela 25 Distribuição Das Diferenças Entre Os Grupos Investunclassified